Chuck. The complete third season [videorecording (DVD)] - Schwartz, Josh, 1976-; Fedak, Chris; Levi, Zachary, 1980-; Strahovski, Yvonne, 1982-; Gomez, Joshua, 1975-; McPartlin, Ryan, 1975-; Lawrence, Mark Christopher, 1964-; Krinsky, Scott, 1968-; Sahay, Vik; Lancaster, Sarah, 1980-; Baldwin, Adam, 1962- (Warner Home Video, 2010)
No more Mr. Nice Spy! Chuck is back and he's the Chuck you know: the hapless Nerd Herder hopelessly devoted to sexy superspy Sarah. And he's the Chuck you don't know: a master martial artist whose brain is locked and loaded with the new Intersect 2.0. How the two Chucks clash, bash, and (sometimes) cooperate makes Season Three total action-packed fun.